2011
DOI: 10.1038/bjc.2011.283
|View full text |Cite
|
Sign up to set email alerts
|

Expression of laminin 5-γ2 chain in cutaneous squamous cell carcinoma and its role in tumour invasion

Abstract: Background:Laminin-5 (Ln5), a heterotrimer composed of three chains (α3, β3, and γ2), is a major component of the basement membrane in most adult tissues. One of the chains, Ln5-γ2, is a marker of invasive tumours because it is frequently expressed as a monomer in malignant tumours. Recent studies from our laboratories detected higher levels of Ln5-γ2 expression in basal cell carcinoma (BCC) than in trichoblastoma. Furthermore, Ln5-γ2 overexpression tended to correlate with aggressiveness in BCC.Methods:In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 22 publications
2
44
0
Order By: Relevance
“…It has been reported that gefitinib inhibits the growth of hepatocellular carcinoma cells, Ln5 reduces the ability of gefitinib to inhibit cell growth and the addition of exogenous Ln5 has no effect on p-EGFR but restores p-Akt (16). Another in vitro study performed using A431 cutaneous squamous cell carcinoma cells reported that Ln5-γ2 siRNA significantly suppressed EGF-stimulated A431 cell invasion (17). In addition, the introduction of Ln5 may activate a survival signal through EGF-independent EGFR activity in certain types of human lung adenocarcinoma cell lines (18).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that gefitinib inhibits the growth of hepatocellular carcinoma cells, Ln5 reduces the ability of gefitinib to inhibit cell growth and the addition of exogenous Ln5 has no effect on p-EGFR but restores p-Akt (16). Another in vitro study performed using A431 cutaneous squamous cell carcinoma cells reported that Ln5-γ2 siRNA significantly suppressed EGF-stimulated A431 cell invasion (17). In addition, the introduction of Ln5 may activate a survival signal through EGF-independent EGFR activity in certain types of human lung adenocarcinoma cell lines (18).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, inhibition of LAMC2 showed reduced cell migration, invasion, wound healing and cell cycle arrest (G1/S phases of cell cycle) of ATC cells [13]. Interestingly, LAMC2 knockdown significantly suppressed the EGF-induced invasion of epidermoid carcinoma cells (A431 cells) [24]. Moreover, cetuximab (EGFR blocking antibody) or EGFR small interfering RNA additively enhanced the antiproliferative effect of LAMC2 knockdown compared to control cells.…”
Section: Role Of Lamc2 In Cancersmentioning
confidence: 99%
“…It has been known for sometime that cancer cells secrete normal as well as novel basement membrane proteins and matrix-modifying enzymes. [109][110][111][112][113] How this may specifically contribute to invasion and tumor metastasis is poorly understood. Just prior to invasion, the AC secretes the conserved extracellular matrix protein hemicentin specifically under the AC in the basement membrane that will be crossed.…”
Section: Invadopodia Are Only One Component Of the Invasion Process Imentioning
confidence: 99%